Seed morphological and morphometric traits as diagnostic tools for species-level classification in Indian Eulophia Lindl. (Eulophiinae; Orchidaceae) - Jadhav, Mayur; Momin, Sobiyanaz; Gurav, Rajaram (Phytotaxa, 2026)
The present study evaluates whether seed morphometric and morphological traits can serve as reliable diagnostic tools for species-level classification within the genus Eulophia. Earlier phylogenetic studies have revealed paraphyly within the genus, indicating unresolved generic boundaries and uncertain relationships within the subtribe Eulophiinae. These contradictions in phylogenetic placement highlight persistent taxonomic challenges, necessitating supplementary morphological approaches to clarify species delimitation and evolutionary relationships. In this context, seed morphology and morphometry offer valuable insights. Using light microscopy and scanning electron microscopy, ten species of Eulophia were analyzed for testa and embryo dimensions, testa-to-embryo volume ratios, air space, and surface ornamentation. Testa length ranged from 0.493–1.619 mm and testa width from 1.586–2.734 mm, with testa-to-embryo volume ratios varying from 3–21, reflecting species-specific patterns. Cluster analysis grouped the species into three major clusters, with E. graminea occupying an intermediate position that linked two groups. In the current study, almost all species having air space exceeded 80%, indicating adaptations for wind-mediated seed dispersal. Importantly, all the species used in this study reflect diverse habitats across India, thereby representing the full range of Eulophia taxa available in the country. Seed morphology supports the taxonomic value of seed traits. The morphometric variation is discussed in the context of dispersal related attributes and their significance as baseline data for the conservation of the genus Eulophia.